Usaha Pembibitan Sapi Perah Di Universitas Andalas - E. Nurdin; Andri Andri (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2012)
The business of Dairy Cattle Breeding in Universiy of Andalas is a science and technology program for innovation and creativity in Campus (Ib-IKK). This is a joint program of HEDG and University of Andalas. In 2012, it has just entered the second year of three-years scheduled. The five dairy cattle breed have brought from Lembang (West Java) at the first year program. And now, Ib-IKK have 3 lactation cows, 2 pregnant cows, 1 bull and 3 heifers.This businesses are prioritized to establish the availability of dairy cow, until the business is ready to supply of dairy cattle breed for the farmer in West Sumatera. This time, the program sold a fresh milk, pasteurized milk and agro-tourism, which is managed by undergraduate student of Faculty of Animal Science, University of Andalas.